Integral spaces in the European Union: Possible trends of the social, economic and technological integration in the Baltic region - Melnikas, Borisas (Journal of Business Economics and Management, 2008)
Regional integration oriented transformations in the Baltic region, as well as the unified social, economic and technological space formation processes are described and analysed. These processes are comprehended as an important factor of further social, economic and technological modernization in the Baltic countries, as a precondition for more intensive and active integration of Baltic economic systems into the European and global economic and technological structures, as well as a knowledge‐based society and knowledge economy creation factor. The arguments determining the idea of the Baltic region community and unity, as well as opposing arguments are evaluated. The main principles of integration in the Baltic region, as well as the possible integration strategies are analysed. The unified social, economic and technological space in the Baltic region as a research area is described.First published online: 14 Oct 2010